The Effect of Mulberry Leaf Tea on Postprandial Glycemic Control and Insulin Sensitivity: A Randomized, Placebo-Controlled Crossover Study - Sukriket, Parivat; Surapong Lookhanumarnjao ,; Bumrungpert, Akkarach (Journal of Pharmacy and Nutrition Sciences, 2016)
Leaves of mulberry (Morus alba, L.) have been one of the prominent herbs widely used by traditional medicine for the treatment of diabetes mellitus. The objective of this study was to evaluate the effect of mulberry leaf tea on postprandial plasma glucose and insulin sensitivity after the ingestion of sucrose solution in non-diabetic subjects. This study was conducted on 14 subjects, with a crossover design. Subjects were initially screened for non-diabetic status (FBS < 126 mg/dL). Subjects were randomized to either mulberry leaf tea or water as control. The drink was consumed 30 minutes prior to oral administration of 75 grams sucrose solution. Blood samples were collected before (time point 0) and after sucrose ingestion at 30, 60, 90, 120, and 150 minutes. The treatment group which received mulberry leaf tea prior to the tolerance test tends to have a lower level of plasma glucose, serum insulin concentrations and AUC0-150 compared to the controlled group, but without significant difference. The mean difference of the incremental glucose level at each time point also tends to be lower for the mulberry group, with significant difference at 30-min time point (p = 0.04). No significant differences were found in insulin sensitivity. Therefore, the consumption of mulberry leaf tea may aid in postprandial glycemic control during the first 30 minutes after meal.